2015
DOI: 10.5489/cuaj.3175
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding due to ectopic varices in a urinary diversion: A multidisciplinary diagnostic and therapeutic challenge

Abstract: The ectopic varices in patients with portal hypertension are those that occur at any level of the gastrointestinal (GI) tract, regardless of the varices that occur at the esophageal level. These ectopic varices account for 2-5% of the causes of GI bleeding varices. The risk of bleeding is quadrupled compared to the esophagogastric area, with a mortality of up to 40%. The transjugular intrahepatic portosystemic shunt, should be considered in cases secondary to recurrent bleeding varices.We present a case report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Bleeding ectopic varices as a result of portal hypertension is a rare cause of hematuria in patients with urinary diversion using an intestinal segment. 1 When hemorrhage occurs, it can become a severe problem and has a mortality rate of 3%. 2 , 3 Importantly, a previous study found that ileal varices were present in 18% of patients with liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding ectopic varices as a result of portal hypertension is a rare cause of hematuria in patients with urinary diversion using an intestinal segment. 1 When hemorrhage occurs, it can become a severe problem and has a mortality rate of 3%. 2 , 3 Importantly, a previous study found that ileal varices were present in 18% of patients with liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%